Estrategias pedagógicas en artes plásticas para el fortalecimiento de la interculturalidad en niños de educación general básica de la unidad educativa Riobamba. - Bejarano Reinoso, Yesenia Magali (2021)
This research has been developed in a methodical and orderly manner. The general objective was to design a proposal of pedagogical strategies in plastic arts to strengthen interculturality in the seventh year of primary General Education of Riobamba Educational Unit. In order to achieve this work, the theoretical bases have been laid by carrying out an analysis of theories, research, and books by various authors. A quantitative approach of non- experimental design and a deductive method was applied, which has made it possible to design two instruments for data collection, a survey applied to teachers in the area of cultural and artistic education, and an observation sheet applied to seventh-year GBS children. Experts in the area validated it through the V of Aiken. The data obtained were tabulated, plotted, analyzed, and interpreted, and it served to raise the conclusions that admitted the creation of the pedagogical guide art. The pedagogical strategies in Visual arts such as artistic drawing, painting, and modeling enable stimulating the student's creative and dynamic thinking and strengthening interculturality in the children the subject of the case study. Similarly, the consultation of expert criteria validated that the proposal complies with the pedagogical-didactic parameters that guarantee its applicability in local and national educational contexts.